Movement disorders in MCT8 deficiency/Allan-Herndon-Dudley Syndrome - Masnada, Silvia; Sarret, Catherine; Antonello, Clara Eleonora; Fadilah, Ala; Krude, Heiko; Mura, Eleonora; Mordekar, Santosh; Nicita, Francesco; Olivotto, Sara; Orcesi, Simona; Porta, Francesco; Remerand, Ganaelle; et al. (Molecular genetics and metabolism, 2022)
MCT8 deficiency is a rare genetic leukoencephalopathy caused by a defect of thyroid hormone transport across cell membranes, particularly through blood brain barrier and into neural cells. It is characterized by a complex neurological presentation, signs of peripheral thyrotoxicosis and cerebral hypothyroidism. Movement disorders (MDs) have been frequently mentioned in this condition, but not systematically studied. Each patient recruited was video-recorded during a routine outpatient visit according to a predefined protocol. The presence and the type of MDs were evaluated. The type of MD was blindly scored by two child neurologists experts in inherited white matter diseases and in MD. Dystonia was scored according to Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS). When more than one MD was present, the predominant one was scored. 27 patients were included through a multicenter collaboration. In many cases we saw a combination of different MDs. Hypokinesia was present in 25/27 patients and was the predominant MD in 19. It was often associated with hypomimia and global hypotonia. Dystonia was observed in 25/27 patients, however, in a minority of cases (5) it was deemed the predominant MD. In eleven patients, exaggerated startle reactions and/or other paroxysmal non-epileptic events were observed. MDs are frequent clinical features of MCT8 deficiency, possibly related to the important role of thyroid hormones in brain development and functioning of normal dopaminergic circuits of the basal ganglia. Dystonia is common, but usually mild to moderate in severity, while hypokinesia was the predominant MD in the majority of patients. •Movement disorders are frequent in patients with MCT8 deficiency.•Dystonia is common, but moderate or mild in severity- Hypokinesia is common and severe, and it appeared to contribute much more to the overall functional disability burden.•Paroxysmal movement disorders may be present, mimic in some case epileptic seizures.